Relato de experiência: reflexões sobre o ensino de história mediado pela educação histórica - (:unkn) unknown (Universidade Federal de Goiás, 2020)
This dissertation aims to report the action research carried out during the Professional Master's course of the Postgraduate Program in History, Catalan Regional. The investigation emerged from the concerns arising from the experience as a teacher. The difficulties faced in the classroom awoke me to the need to problematize questions about the teaching and learning of students in the discipline of History. For that, I used Cultural History as a theoretical support to think about History, Historical Education as a methodological support to problematize the development of activities that involved an action research perspective and the experience report as a way of presenting the work. The investigation concluded that, playing the role of mediation, the teacher offers students more autonomy. Working with methodologies such as the Classroom, for example, using Local History for this, provides students with the process of reflecting on their experiences and brings them closer to historical learning, and, finally, promotes the recognition of students as historical subjects.
Experience report: reflections on history teaching mediated by historical education
Keywords: Ensino e aprendizagem; Pesquisa-ação; Educação histórica; Relato de experiência; Teaching and learning; Action research; Historical education; Experience report; CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL